Intraoperative microelectrode recording in Parkinson's disease subthalamic deep brain stimulation: Analysis of clinical utility. (November 2019) - Soares, Maria Inês; Soares-dos-Reis, Ricardo; Rosas, Maria José; Monteiro, Pedro; Massano, João
Highlights: The added value of microelectrode recording (MER) is unclear in STN DBS. Agreement between MER and final electrode position is fair. Agreement between intraoperative stimulation and final electrode position is high. MER might not provide added benefit in Parkinson's patients having awake STN DBS. These results support and inform further prospective randomized controlled research. Abstract: This retrospective study aims to explore the clinical utility of microelectrode recording (MER) during subthalamic deep brain stimulation (DBS) surgery in patients with Parkinson's disease (PD). We analyzed the data from 103 PD patients, who consecutively received bilateral subthalamic nucleus (STN) DBS at an experienced academic medical center. We collected demographic, clinical, and DBS related data, including intraoperative microelectrode recording data, electrode positioning, and clinical effects provided by intraoperative microstimulation. The 2 brain sides were independently analyzed and are described as first and second side (to be operated on); the first side is contralateral to motor symptoms onset. Patients were mostly men (64.1%). In both sides of the brain, percentage of agreement with the electrode final position was higher with clinical results than with intraoperative microelectrode recordings (98% vs 57% on the first implantation side, and 97% vs 58% on the second implantation side, respectively). Regarding electrode final implantation depth, 86% of electrodes were implanted between 0 mm and +2 mm in relation to anatomical target, and 95% of electrodes were implanted from −2 mm to +2 mm. Our study suggests that MER might not be necessary to achieve good clinical outcomes in PD patients undergoing STN DBS. These results support and inform the design of future prospective controlled research studies.